BS EN ISO/IEC 27013:2021/Amd 1 Information security, cybersecurity and privacy protection. Guidance on the integrated implementation of ISO/IEC 27001 and ISO/IEC 20000-1. Amendment 1. (15th September 2023) - British Standards Institution,
No abstract available